Public - Private Partnerships in Healthcare: A Literature Review - Doua, Wissal; Khariss, Mohammed (European Scientific Journal, ESJ, 2026)
As fiscal pressures intensify and healthcare needs continue to rise, public-private partnerships have evolved into a central policy response to close enduring gaps in infrastructure, financing, and service efficiency. This paper presents an integrative literature review of PPPs in healthcare sector, exploring their theoretical foundations and examining their conceptual underpinnings and the empirical results. Based on evidence from scholarly publications, institutional analyses, and international policy sources, the review highlights findings across diverse contexts from both advanced and developing economies. Findings reveal that PPPs can markedly advance healthcare access, efficiency, and quality when backed by strong institutional capacities, clear governance mechanisms, and fair risk sharing. While case studies from Morocco, Iran, and Lesotho demonstrate the positive impact of PPPs on hospital functioning and patient care, other studies underscore persistent challenges such as budgetary exposure, governance deficits, and the growing financialisation of the healthcare sector. According to the study, PPPs should not be viewed as a universal solution but rather as a governance approach whose success relies on robust state capacity, sound regulatory frameworks, and consistent policy alignment. When thoughtfully designed and efficiently implemented, PPPs can enhance the pursuit of equitable, efficient, and durable healthcare systems, notably within settings facing fiscal and infrastructural constraints.